ᵓṣḫ in the Ancient North Arabian Inscriptions (Safaitic) - رعوان, شيرين (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The research highlights on the verb "A-S-Kh" in the ancient north Arabic inscriptions through three new inscriptions published for the first time. They were transferred to the classical Arabic language and they studied the nouns, the verbs, and vocabularies contained therein. They also were compared with other ancient oriental inscriptions and with all the Safaitic inscriptions known so far .Those inscriptions were the most prominent thing left to us by the people of the Arabian peninsula in the two centuries (the 2nd century AD and the 4th century BC ).They were truly a mirror of the community of Arab tribes which are spread in southern Syria,northeasten Jordan ,western Iraq, and northwestern Saudi Arabia . These inscriptions are among the most discovered ones ,as nearly 35000 inscriptions have been found in the rocks .They also formed the first yeast or early childhood for the development of the Arabic letter in which we write so far .The research concluded that most of the verbs in the Safaitic inscriptions refer ta sadness and they are related to the environment of the owners of these inscriptions .